Strategi Komunikasi Rumah Sakit Ibu dan Anak Bahagia dalam Memberikan Pelayanan Kepada Pasien - Baharuddin Sunu; Anita Anita (Lontara Journal of Health Science and Technology, 2022)
The Bahagia Mother and Children Hospital in Makassar is a privately owned health service in the form of a maternity hospital. To improve the quality of patient health services at the Bahagia Mother and Children Hospital Makassar, it is necessary to take appropriate communication strategies. This research method uses descriptive qualitative research with a location in the Bahagia Mother and Child Hospital Makassar. The results of this study indicate that at the Bahagia Mother and Child Hospital Makassar, a communication strategy has been carried out in providing services to patients, including through competent medical/non-medical services, effective communication by medical/non-medical staff to patients through the application of a friendly 6S attitude in serving patients, health services that reach all aspects of society, the availability of health information banners and hospital services, making health information leaflets, procuring suggestion boxes, and using Facebook and YouTube to reach the wider community. Based on the results of this study, it can be concluded that the Bahagia Mother and Child Hospital Makassar has implemented a communication strategy in providing services to patients.